Prospects of limiting the right to reproductive health in South Africa : a human wellbeing and socio-economic view - Matsheta, R. M. (University of Limpopo, 2019)
Like many other countries, South Africa has its own socio-economic challenges. For the past two decades, the country has been experiencing rapid population growth, yet in the same period, there has been a pervasive decline in social and economic stability, and in the end, stagnant human wellbeing. This has been as a result of diminishing access to basic services such as health care, quality housing, quality education and safe clean drinking water. Among other factors, unregulated and rapid population growth contribute to these socio-economic challenges. This study seeks to illustrate that overpopulation undermines and threatens social development, societal stability and survival of humanity. Therefore, the examines the possibility of enacting a legislation or policy that will regulate or limit procreation or the right to give birth. It also reflects on the Chinese experience to obtain some lessons from China’s One-Child Policy. It is submitted that South Africa must draft its own policy or legislation that will regulate population growth with the primary objective of aligning population with available state resources. Keywords: overpopulation, right to reproductive health, socio-economic rights, human wellbeing, social transformation.
Thesis (M. Law. (Development and Management)) --University of Limpopo, 2019
Keywords: Right to reproductive health; Socio-economic conditions; South Africa; Overpopulation; Human wellbeing; Social transformation; Reproductive healthe -- South Africa; Reproductive healthe - Law and legislation; Reproductive rights